2018
DOI: 10.11646/zootaxa.4501.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Raoiella of the world (Trombidiformes: Tetranychoidea: Tenuipalpidae)

Abstract: We describe 16 new species and redescribe six established species in the genus Raoiella—R. argenta sp. nov. Beard, R. australica Womersley, R. bauchani sp. nov. Beard & Ochoa, R. calgoa sp. nov. Beard & Ochoa, R. crebra sp. nov. Beard & Ochoa, R. davisi sp. nov. Beard, R. didcota sp. nov. Beard, R. eugeniae (Mohanasundaram), R. goyderi sp. nov. Ochoa & Beard, R. hallingi sp. nov. Beard, R. illyarrie sp. nov. Beard & Ochoa, R. indica Hirst, R. karri sp. nov. Ochoa & Beard, R. macfarlanei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Additionally, numerous species were subsequently described from India and Pakistan [ 10 , 11 , 12 , 13 , 14 ]. Most of the valid species described are from Australia, with three species from India (including R. indica ), one species from South Africa, and one species from Greece [ 15 ]. The genus is divided into five species groups, with R. indica and Raoiella pandanae Mohanasundaram composing the R. indica group, which are also the only species known to feed on monocotyledon plants [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, numerous species were subsequently described from India and Pakistan [ 10 , 11 , 12 , 13 , 14 ]. Most of the valid species described are from Australia, with three species from India (including R. indica ), one species from South Africa, and one species from Greece [ 15 ]. The genus is divided into five species groups, with R. indica and Raoiella pandanae Mohanasundaram composing the R. indica group, which are also the only species known to feed on monocotyledon plants [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the valid species described are from Australia, with three species from India (including R. indica ), one species from South Africa, and one species from Greece [ 15 ]. The genus is divided into five species groups, with R. indica and Raoiella pandanae Mohanasundaram composing the R. indica group, which are also the only species known to feed on monocotyledon plants [ 15 ]. Recent studies have indicated that many of the described Raoiella species from the Indian subcontinent were actually junior synonyms of R. indica [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations